Youth activism and dignity in post-war Mostar – envisioning a shared future through heritage. Issue 2 (4th May 2019) - Wollentz, Gustav; Barišić, Marko; Sammar, Nourah
ABSTRACT: This paper looks at youth activism in Mostar through a specific action occurring in 2016, when an electric substation was overpainted in the neighbourhood of Rudnik. The project highlighted the rights of the miners to emphasize that other than ethnic identities can be brought forward through cultural heritage. The paper aims to broaden the spectrum of heritage values to encompass the concept of dignity. The monument served to induce a sense of dignity on two levels. Firstly, people were given the agency to influence the monument. Secondly, the monument emphasized workers' identity, which is currently silenced in the public space.